Directed improvisation: how governments can guide creative problem-solving without dictating outcomes - Ang, Yuen Yuen (Henry Stewart Talks, 2024)
Directed improvisation, Government policy, Innovation, China, USA, Neoliberalism, Interventionism, Uncertainty, Industrial mindset, Creative mindset